Bile acids and apoptosis modulation - Ramalho, Rita M. (2015)
The potential role of apoptosis in Alzheimer's disease (AD) has been an area of intense research in recent years. Ursodeoxycholic acid (UDCA) and its taurine-conjugate, tauroursodeoxycholic acid (TUDCA) are endogenous bile acids that act as potent inhibitors of apoptosis. Their therapeutic effects have been tested in many experimental pathological conditions, including neurological disorders, such as AD. TUDCA regulates precise transcriptional and post-transcriptional events that impact mitochondrial function in neurons. TUDCA not only stabilizes the mitochondrial membrane and prevents Bax translocation, inhibiting the release of cytochrome c and the activation of caspases, but also interferes with upstream factors, including cell cycle-related proteins. In addition, TUDCA is capable of inducing survival pathways. Here, we review the role of apoptosis in AD and discuss the therapeutic potential of TUDCA in treating this disease.